Test-driven development for iOS : using continuous integration and continuous delivery - Shum, Cassie (LiveLessons., 2016)
"Continuous Delivery (CD) is an agile practice that's had a big impact on how many people think about developing software. It forced us to start thinking that software is only done when it is released. With more features reaching the done stage sooner, CD practices have enabled us to get early feedback from users and taught us a lot about testing, monitoring, and automating our delivery along the way. But mobile development has often been left behind. Or has it? Testing is an important component of CD and shouldn't be taken for granted or ignored, especially when developing mobile applications for iOS. The process of setting up a testable environment and writing tests, however, can be a challenge. Implementing unit tests and following principles of test-driven development (TDD) for mobile apps--whether native or hybrid--is often counterintuitive. To guarantee that each component in your mobile app works properly for the set of inputs you expect, it is important to test each component (or unit) of an architecture independently and to simulate different system states based on the supplied input to the test, while covering exotic cases in the process."--Resource description page.